Дистанційна вища технічна освіта в умовах карантину - Козлакова Галина; Сусь Богдан; Коваленко Оксана; Іванова Юлія; Ставицька Ірина; Kozlakova Galina; Sus Bogdan; Kovalenko Oksana; Ivanova Julia; Stavitska Iryna (Видавництво «Педагогічна преса», 2020)
Резюме. Система української вищої освіти навесні 2020 р. опинилася у надзвичайній ситуації, коли було необхідно витримувати умови карантину внаслідок вірусної епідемії та шукати можливості не втратити навчальний рік. Більшість університетів обрали он-лайн навчання, отже, таким чином забезпечили дистанційне спілкування викладачів і студентів та електронний за рівнем знань. Особливості організації навчального процесу в умовах карантину досліджує колектив авторів даної статті, кожен з яких працює в різних технічних університетах (НТУУ "Київський політехнічний інститут імені Ігоря Сікорського", Національний університет біоресурсів і природокористування та інших). Представлено здобутки і методики використання різних освітніх платформ для створення навчальних курсів, комунікації викладачів і студентів і контролю досягнень осіб, які навчаються. Аналіз названих вище особливостей та перспективні можливості розвитку такого виду дистанційного навчання на основі використання різних комп'ютерних платформ пропонуються в даній статті.

Abstract. System of Ukrainian higher technical education on the spring of 2020 was in specific situation when it was necessary to fulfil conditions of virus quarantine and to find the possibilities not to lost an educational year. The most of universities organized on-line education and in this way created distance communication of professors with students and electronic control of educational results. Several specific features of organization educational process in conditions of virus quarantine were analyzed by an author’s collective of this article. Each author works at one of technical university (NTUU “Kiev Polytechnic Institute named after Igor Sikorskiy ”, National University of Nature Resources of Ukraine and others). There are characterized an experience and methodological approaches to using different educational platforms for creation of educational courses, communication of educators and students and control of achievements of those who study at different universities.. Professors and educators of Kiev Polytechnic Institute named after Igor Sikorskiy were prepared for this work by special training in Ukrainian Institute of Information Technologies in Education as special Department of the university. At the same time they were used famous in the World systems of Internet-communication such as Moodle, Zoom, Cisco Systems, Coursera, Google classroom so on. New platform “Sikorskiy” (created on the base of Moodle) was successful used for study of special courses in on-line education. National University of Nature Resources of Ukraine is represented by the successful experience and on-line work of Higher Mathematics Department. Positive and negative features of this work in system E-learn are described. Specific of distant educational work with groups of students in conditions of quarantine was shown at the end of article with using of special handbook in physics (with electronic representation.). An analyze of various specific features and perspectives of improvement and expansion of such kind of educational process with using of different types of computer platforms and Internet resources was represented in this article too. The authors watch for new level of educators qualification and new discussions during new science-pedagogical conferences on these themes.
Distant technical education in conditions of quarantine
Keywords: дистанційна освіта; освітні платформи; он-лайн навчання; távoktatás; oktatási platformok; online tanulás